(untitled) (AYUSHDHARA, 2025)
Coronary Artery Disease (CAD) is a leading cause of premature death. The incidence of cardiac disease is increasing in an alarming rate in our society due to sedentary lifestyle, faulty diet and mechanical life as an impact of western culture. One in 4 deaths in India is due to CAD. Objective: To assess the efficacy of Deepana-pachana, Virechana, Hridbasti and Rasayana-prayaga in spectrums of CAD. Methodology: Prospective, randomised, open labelled modern controlled clinical experimental study. Diagnosed cases of CAD with conditions were treated with Deepana-pachana with Shaddharana Yoga, Mrudu-snehapana with Punarnavadi Taila followed by Virechana, Hridbasti with Punarnavadi Taila, and Rasayana Yoga like Shilajatuguggulu swarnamakshika Rasayana and Arjuna pushakara moola chatushparni Churna in above said spectrum of CAD. Result: Subjective parameters like Hridshoola, Swasavarodha, etc and objective parameters like lipid profile, blood pressure, homocysteine, ECG and ECHO have shown improvement as shown in the table. Conclusion: Coronary artery disease is a clinical syndrome in which atherosclerotic coronary arteries are responsible for inability of cardiac muscle to pump the blood throughout the body and is a leading cause of MI, ACS, heart failure, and other complications. In this cases series encouraging results were reported. This treatment protocol can be adopted in CAD with respect to Kapha-vata-pradhana Tridoshaja Hridroga in routine Ayurvedic practice.